The role of social networks in migrant access to housing in Lenasia - Desai, Anisa (My University, 2009)
Migrant social networks have become somewhat of a trademark of global migration. Social networks and their development cannot only be recognized as a by product of migration, instead what has been noted is that social networks have emerged as primary actors in the migration process as seen in the incidence of the Asian migrant population in Lenasia. The use of social networks by migrants allow for migrants to accrue a range of benefits such as access to accommodation, employment, security and participation in social activities. With regard to the research report, the use of social networks by Asian migrants to access accommodation in Lenasia has been the focus of the study. Initial assumptions about this transient community entailed that migrants in Lenasia were generally unable to access accommodation through other formalised mechanisms such as rental companies therefore they relied on social networks. This has however been proven incorrect and what was found was that the migrant population had in fact never considered or utilised the services of a rental company because their social networks had always successfully met their accommodation needs. The occurrence of migrant social networks in Lenasia has initiated further migration into the area, and subsequently led to the development of migrant enclaves operating in isolation from the pre-existing community. The effect the creation of migrant enclaves in Lenasia has had on the area’s development trajectory is explored in the research. In addition the consequences of migrant enclaves and separate social networks between the pre-existing and migrant community are investigated
Keywords: Housing; South Africa; Migrants; Social networks